Patients With Electrical Status Epilepticus in Sleep Share Similar Clinical Features Regardless of Their Focal or Generalized Sleep Potentiation of Epileptiform Activity. (January 2013) - Fernández, Iván Sánchez; Peters, Jurriaan; Takeoka, Masanori; Rotenberg, Alexander; Prabhu, Sanjay; Gregas, Matt; Riviello, James J.; Kothare, Sanjeev; Loddenkemper, Tobias
The study objective was to compare qualitatively the clinical features of patients with electrical status epilepticus in sleep with focal versus generalized sleep potentiated epileptiform activity. We enrolled patients 2 to 20 years of age, studied between 2001 and 2009, and with sleep potentiated epileptiform activity defined as an increase of epileptiform activity of 50% or more during non–rapid eye movement sleep compared with wakefulness. Eighty-five patients met the inclusion criteria, median age was 7.3 years, and 54 (63.5%) were boys. Sixty-seven (78.8%) patients had focal sleep potentiated epileptiform activity, whereas 18 (21.2%) had generalized sleep potentiated epileptiform activity. The 2 groups did not differ with respect to sex, age, presence of a structural brain abnormality, epilepsy, or other qualitative cognitive, motor, or behavioral problems. Our data suggest that there are no qualitative differences in the clinical features of patients with focal versus generalized sleep potentiated epileptiform activity.